1968
DOI: 10.1002/dev.420010212
|View full text |Cite
|
Sign up to set email alerts
|

Mother‐infant interactions and experimental manipulation: Confounding or misidentification?

Abstract: MEIER, GILBERT W., and SCHUTZMAN, LLOYD H. (1968). Mother-infant Interactions ond Experimental MonipulationrConfounding or Misidentification? DEVELOPMENTAL PSYCHOBIOLOGY, l(2): 141-145. T h e role of material responsiveness to offspring behaviors in the research on early experience and behavioral development is discussed. T h e proposition is offered that the behavioral changes following experimenter nianipulation of the offspring during the preweaning period, as by handling. isolation, shock stimulation, or c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
23
0

Year Published

1970
1970
2006
2006

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(26 citation statements)
references
References 20 publications
3
23
0
Order By: Relevance
“…This indicates that some characteristic of the maternal environment that varied between the AI J and CS7B1I6J strains was essential for each of these consequences of early handling. Therefore, our results provide strong support for the hypothesis of maternal mediation of early-stimulation effects (Barnett & Burn, 1967;Meier & Schutzman, 1968;Richards, 1966).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…This indicates that some characteristic of the maternal environment that varied between the AI J and CS7B1I6J strains was essential for each of these consequences of early handling. Therefore, our results provide strong support for the hypothesis of maternal mediation of early-stimulation effects (Barnett & Burn, 1967;Meier & Schutzman, 1968;Richards, 1966).…”
Section: Discussionsupporting
confidence: 80%
“…Some early suggestions, such as that corticosterone released during early stimulation acts on the brain to reduce later emotionality (Denenberg & Zarrow, 1971) or that the hypothermia induced by the early manipulation accounts for the later effects (Schaefer, Weingarten, & Towne, 1962), have since fallen into disfavor (e.g., Ader & Grota, 1973;Thoman & Levine, 1969). A hypothesis that has been gaining support in recent years is that the mother's differential treatment of manipulated and nonmanipulated pups mediates at least some early-stimulation effects (Barnett & Burn, 1967;Meier & Schutzman, 1968;Richards, 1966). It has been amply demonstrated that maternal behavior varies with the treatment (e.g., handling, shock, nonmanipulation) of the infant mouse or rat (Barnett & Burn, 1967;Bell & Little, 1978;Bell, Nitschke, Bell, & Zachman, 1974;Lee & Williams, 1975;Priesinall, 1973;Sherrod, Connor, & Meier, 1974;Smotherman, Brown, & Levine, 1977;Young, 1965).…”
mentioning
confidence: 99%
“…In fact, the rodent dam is sensitive to the changing stimulus qualities of the pups (Meier and Schutzman, 1968;Young, 1965) and shows systematic changes in maternal behavior depending on the nature of the treatment that the offspring have received (Barnett and Burn, 1967;Bell et al, 1974) and the time during lactation in which the manipulations occur (Smotherman et al, 1977a, b). It has been demonstrated that heightened maternal behavior results from pup cues elicited by more intense treatments such as electric shock (0.4 mA) (Smotherman et al, 1977a, b).…”
Section: Discussionmentioning
confidence: 99%
“…Although these findings seem to lead to a compelling conclusion that the more maternal care offspring receive, the greater functional advantage they have during adulthood, it has long been noted in the literature on rodents that early stimulation of the mother and stimulation of pups are intrinsically confounded in neonatal handling studies because dams of handled pups are removed from the litter during the procedure (11)(12)(13)(14). Because mothers of handled pups are likely to change their care behavior toward pups as a result of this experience, correlations between maternal care and changes in offspring behavioral and neuroendocrine measures (8) could be the result of a direct stimulation effect on pups, an indirect effect on pups due to stimulationinduced alterations in maternal care, or both.…”
mentioning
confidence: 99%